Elevated CO2-Mitigation of High Temperature Stress Associated with Maintenance of Positive Carbon Balance and Carbohydrate Accumulation in Kentucky Bluegrass - Song, Yali; Yu, Jingjin; Huang, Bingru (PloS one, 2014)
Elevated CO2 concentration may promote plant growth while high temperature is inhibitory for C3 plant species. The interactive effects of elevated CO2 and high temperatures on C3 perennial grass growth and carbon metabolism are not well documented. Kentucky bluegrass (Poa pratensis) plants were exposed to two CO2 levels (400 and 800 μmol mol-1) and five temperatures (15/12, 20/17, 25/22, 30/27, 35/32°C, day/night) in growth chambers. Increasing temperatures to 25°C and above inhibited leaf photosynthetic rate (Pn) and shoot and root growth, but increased leaf respiration rate (R), leading to a negative carbon balance and a decline in soluble sugar content under ambient CO2. Elevated CO2 did not cause shift of optimal temperatures in Kentucky bluegrass, but promoted Pn, shoot and root growth under all levels of temperature (15, 20, 25, 30, and 35°C) and mitigated the adverse effects of severe high temperatures (30 and 35°C). Elevated CO2-mitigation of adverse effects of high temperatures on Kentucky bluegrass growth could be associated with the maintenance of a positive carbon balance and the accumulation of soluble sugars and total nonstructural carbohydrates through stimulation of Pn and suppression of R and respiratory organic acid metabolism.